The Migratory Cycle of Images: Reactivation Strategies in Contemporary Artistic Productions - Mudu, Stefano (Elephant & Castle, 2023)
Since the 1990s, an increasing number of artists, curators, dancers, choreographers and other professionals of the cultural panorama have looked at reality with an extractive approach: they have used objects already in circulation in the artistic context and re-proposed them in the present by adjusting them on a formal and/or content level. With the aim of analysing the consequences of these reactivation strategies, the essay intends to outline the importance of the so-called “re-enactment studies” which have hitherto dealt with the subject, and it then discusses the utility of a novel analytical model called “migratory cycle of images”. The latter proposes to approach a generic act of reactivation in operational terms, identifying the role that images play in the various phases of the process. Finding proper support in contemporary philosophical theories such as Object-Oriented Ontology and in the analysis of some exemplary artistic productions, this operation allows to: question the terminology currently used in the field, arrive at the formulation of new nomenclatures, and, finally, outline the boundaries of the “enactment studies”, along with different prefixes to differentiate the multiform methods of re-generating the existing.